KEJAKSAAN SEBAGAI PEMOHON DALAM MENGAJUKAN KEPAILITAN - Yenny Febrianty Febrianty (Universitas Pakuan, 2020)
ABSTRACT Prosecutors with special powers can act inside or outside the court for and on behalf of the state or government. Based on the provisions in Article 2 paragraph (2) Law Number 37 of 2004 in conjunction with Government Regulation Number 17 of 2000, it is stipulated that the Prosecutor's Office as one of the parties that can file bankruptcy, with the conditions that must be met is that no other party submits a similar application for the sake of public interest. Therefore, it is necessary to strengthen the implementation of the Attorney's Office's authority as a petitioner in filing for bankruptcy in the midst of Indonesian society so that the general public's understanding of the Attorney's authority can be applied and beneficial to people who are about to go bankrupt. The law under study is the ius constitendum. The data used are primary data and secondary data, data collection techniques are interview data collection and library materials. The implementation of the exercise of the authority of the Attorney General's Office as an applicant in bankruptcy for the sake of the public interest is regulated in the applicable laws and regulations. The provision which states that an application for bankruptcy in the public interest can only be carried out if there is no party filing an application for bankruptcy, it is best if an exception is granted by the legislators, in the event that the Attorney requests bankruptcy for the public interest involving the interests of the state, the Prosecutor's Office should be empowered to act on behalf or as proxies. from state institutions that directly have debts and receivables against Debtors, so that institutions that have a direct relationship between debts and debtors do not think that the AGO is working independently without paying attention to the interests of the institution. Keywords: Attorney General's Office, Petitioner, Bankruptcy ABSTRAK Kejaksaan dengan kuasa khusus dapat bertindak di dalam maupun di luar pengadilan untuk dan atas nama negara atau pemerintah. Berdasarkan ketentuan dalam Pasal 2 ayat (2) Undang-Undang Nomor 37 Tahun 2004 jo Peraturan Pemerintah Nomor 17 Tahun 2000 diatur bahwa Kejaksaan sebagai salah satu pihak yang dapat mengajukan kepailitan, dengan persyaratan yang harus dipenuhi adalah tidak ada pihak lain yang mengajukan permohonan serupa demi kepentingan umum. Oleh karena itulah perlu kiranya memperkuat implementasi kewenangan Kejakasaan ini sebagai pemohon dalam mengajukan kepailitan di tengah masyarakat Indonesia sehingga pemahaman masyarakat umum terhadap kewenangan Kejaksaan tersebut dapat diterapkan dan bermanfaat bagi masyarakat yang akan berpekara kepailitan tersebut. Hukum yang dikaji adalah ius constitendum. Data yang digunakan adalah data primer dan data sekunder, teknik pengumpulan data berupa pengumpulan data wawancara dan bahan-bahan perpustakaan. Implementasi pelaksanaan kewenangan Kejaksaan sebagai pemohon dalam kepailitan demi kepentingan umum diatur dalam aturan per Undang-Undangan yang berlaku. Ketentuan yang menyatakan permohonan pailit untuk kepentingan umum hanya dapat dilakukan apabila tidak ada pihak yang mengajukan permohonan pailit sebaiknya diberikan pengecualian oleh pembuat undang-undang, dalam hal Kejaksaan memohon pailit untuk kepentingan umum yang menyangkut kepentingan negara Kejaksaan sebaiknya diberi wewenang untuk bertindak mewakili atau sebagai kuasa dari lembaga negara yang secara langsung memiliki utang piutang terhadap Debitor, agar lembaga yang secara langsung memiliki hubungan utang piutang terhadap Debitor tidak menganggap Kejaksaan bekerja secara mandiri tanpa mengindahkan kepentingan dari lembaga tersebut. Kata kunci: Kejaksaan, Pemohon, Kepailitan